The Influence of Principal’s Leadership and Teacher’s Work Motivation on Teacher’s Work Discipline - Andiani, Weni; Fitria, Happy; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aimed to determine and identify: (1) the influence of principal leadership on teacher work discipline; (2) the effect of work motivation on teacher work discipline; and (3) the influence of principal leadership and work motivation together on teacher work discipline. The data in this study were collected through distributing questionnaires to respondents. The results of filling out the questionnaire were analyzed using multiple regression analysis through the t-test, F-test, and determination coefficient test. The population in this study were all junior high school teachers in the Sako Palembang sub-district, totaling 144 people. The sampling technique in this study is probability sampling using the Slovin formula to obtain 106 teachers as the research sample. The results of the study found that: (1) there is a significant influence between the principal’s leadership on teacher work discipline; (2) there is a significant influence between work motivation on teacher work discipline; (3) there is a significant influence between principal leadership and work motivation on teacher work discipline.